A cross-sectional study on the practice of wet nursing among Muslim mothers - C. A. R. Norsyamlina; H. Salasiah Hanin; A. M. Latifah; K. Zuliza; M. H. Nurhidayah; S. Rafeah; B. Nora'inan; I. Muhamad Zariff; A. Noor Ani (BMC, 2021)
Abstract Background Breastfeeding and wet nursing have been synonymous since ancient times. The practice of wet nursing of another woman's child in Malaysia is on the rise due to the emergence of awareness among the public about the importance and advantages of breast milk. However, problems arise when there is no systematic system to record and trace the milk mother and milk child data, especially for Muslim participants as milk kinship could affect their relationship status in Islam. Therefore, this study aims to determine the practice of wet nursing among Muslim mothers in Selangor. Simultaneously, this study intends to provide the authorities with an accurate picture of the more aggressive compilation of steps to prevent duplication of consanguinity in wet nursing. Methods This cross-sectional study was conducted on 100 women who had breastfed another child in Selangor. Data were obtained using a validated questionnaire (Cronbach alpha = 0.8) and processed using the SPSS software. Results Results showed 43.0% of respondents had at least breastfed one someone else's child. Meanwhile, there were 3.0% of the respondents were nursing seven to ten other children. A total of 237 children have been breastfed by the respondents (n = 100). Of these, 21.5% children were breastfed less than five times, while 78.5% children were breastfed less than five times. Most mothers recorded their milk child background data, and this shows that the community is aware of the importance of data documentation and it indirectly proves that the authorities should act on these current needs. Conclusions This study shows that there is a wet nursing practice in the society. Obviously, a phenomenon, trend and practice in the society has the ground and basis as to why it existed and is upheld. Researches related to wet nursing and matters connected to it should continue so as to bring about much good to society.